PENCITRAAN KAWASAN WISATA KUTA LOMBOK TENGAH - Jumail, Mohamad (Jurnal Ilmiah Pariwisata; Volume 2 No.1 Hal 109-222 September 2012)
This research is descriptive, where the essence isability in displaying “a picture” of tourism phenomenon from the past, the present, to the future. Therefore, qualitative approach is good choice. The respondent are tourists which had determined by quote sampling and for the stakeholders determined by purposive sampling. Moreover, the data is gathered by observation, interview, questionnaire, literature review, documentation and focus group discussions which analyzed by qualitative-interpretative and quantitative with Likert scales. Thus, all analysis were presented in diagram, chart, picture, photo, and narration or statements as well. Based on The tourists image (pre—in site—post) visiting shown a positive trend, positive image were increasing and decreasing in negative image. The components of image for international tourist dominated by functional—psychology patterns, unique—holistic as its attributes. Differs to domestic tourist where psychology—functional as the pattern and, the attribute were similar to international tourists. Based on image formation, Kuta Lombok Tengah destination mainly formed by organic image, but modified imagery were not significantly contribute. Finally, several aspects which must be put on top priority in terms of tourism image improvement are accessibilities, amenities, the cleanliness of the beaches and the aggressively of the hawkers as well
Keywords: imagery, tourist, destination